Use of aromatic and medicinal plants, drugs and herbal products in Bragança city - Cheio, Mónica (2019)
Herbal therapy is characterized by the use of aromatic and medicinal plants (AMP) in different pharmaceutical forms for therapeutic purposes. The present study aims to characterize the use of AMP, drugs and herbal products in Bragança city.